The value of a sum

Algebra Level 2

For real numbers a , b , c a,b,c , where a b , a c , b c a\ne b, a\ne c, b\ne c , there holds a b c + b c a + c a b = 0 \dfrac a{b-c}+\dfrac b{c-a}+\dfrac c{a-b}=0 . The value of the sum a ( b c ) 2 + b ( c a ) 2 + c ( a b ) 2 \dfrac a{(b-c)^2}+\dfrac b{(c-a)^2}+\dfrac c{(a-b)^2} is


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

From the condition there follows a b c = b c a + c a b -\dfrac a{b - c} = \dfrac b{c - a} + \dfrac c{a - b} . So a ( b c ) 2 = a b c ( a b ) ( c a ) -\dfrac a{(b - c)^2} = \dfrac{a-b-c}{(a - b)(c-a)} . Similarly, b c a = a b c + c a b -\dfrac b{c - a} = \dfrac a{b - c} + \dfrac c{a - b} implies b ( c a ) 2 = a + b c ( a b ) ( b c ) -\dfrac b{(c - a)^2} = \dfrac{-a + b - c}{(a - b)(b - c)} . Also, from c a b = a b c + b c a -\dfrac c{a - b} = \dfrac a{b - c} + \dfrac b{c - a} , we have c ( a b ) 2 = a b + c ( c a ) ( b c ) -\dfrac c{(a - b)^2} = \dfrac{-a - b + c}{(c - a)(b - c)} . Summing the left-hand sides and the right-hand sides, we obtain a ( b c ) 2 b ( c a ) 2 c ( a b ) 2 = a b c ( a b ) ( c a ) + a + b c ( a b ) ( b c ) + a b + c ( c a ) ( b c ) -\dfrac a{(b - c)^2} -\dfrac b{(c - a)^2} -\dfrac c{(a - b)^2} = \dfrac{a-b-c}{(a - b)(c-a)} + \dfrac{-a + b - c}{(a - b)(b - c)} + \dfrac{-a - b + c}{(c - a)(b - c)} . However, a b c ( a b ) ( c a ) + a + b c ( a b ) ( b c ) + a b + c ( c a ) ( b c ) = ( b c ) ( a b c ) + ( c a ) ( a + b c ) + ( a b ) ( a b + c ) ( a b ) ( b c ) ( c a ) = 0 \dfrac{a-b-c}{(a - b)(c-a)} + \dfrac{-a + b - c}{(a - b)(b - c)} + \dfrac{-a - b + c}{(c - a)(b - c)}= \dfrac{(b-c)(a-b-c)+ (c - a)(-a + b - c) +(a - b)(-a - b + c)}{(a - b)(b - c)(c - a)}=0 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...